Nesting Of Montezuma Quail In Mexico - David García-Solózano; Carlos González-Rebeles Islas; German D. Mendoza Martínez; Ernesto Ávila González; Fidel Hernández (National Quail Symposium Proceedings, 2022)
Although Mexico has the greatest diversity of quail of any New World country, basic information on the ecology and life history of Mexican quails remains unknown. Our objective was to describe nest characteristics of the Montezuma quail (Cyrtonyx montezumae montezumae) in central Mexico. We searched for Montezuma quail nests within 8 counties in the state of México, Mexico during May–September 2003. We conducted nest searches along 66 transects (3–5 km × 40 m) distributed across 17 study sites. We recorded vegetation community, elevation, and nesting substrate for each nest. We measured nest characteristics: height, depth, nest entrance diameter, and orientation. If eggs were found, we recorded clutch size and egg mass, texture, color, and shape. We observed 324 quail and located 6 nests along a 254-km route. Nests were located at elevations ranging from 2,568–2,692 m above sea level. Mean (± standard deviation) nest height and depth were 122.2 ± 7.7 mm and 195 ± 61.8 mm, respectively. Nest entrance orientation for 5 of 6 nests was toward a southerly direction. Mean nest egg mass was 9.9 ± 0.1 g. Our study provides basic and descriptive information on a poorly known quail species in Mexico.
Keywords: Cyrtonyx montezumae; Montezuma quail; nesting; Odontophoridae; central Mexico